Do Menstrual Hygiene Practices, Premenstrual Syndrome, and Mood Swings differ for Female Students in Sports with those Non-Sports Extracurriculars ? - Zahro, Siti Fatimatuz; Mustar, Yetty Septiani; Susanto, Indra Himawan; Kumaat, Noortje Anita (Journal of Sport and Exercise Science, 2024)
Purpose: Menstrual health is a significant component of women's lives that is frequently disregarded, particularly when it comes to extracurricular activities. The objective of this study is to identify disparities in menstrual hygiene practices, premenstrual syndrome, and mood swings among female students who participate in sports and those engaged in non-sports extracurricular activities. Materials and Methods: This cross-sectional study involved 129 female students in senior high school, consisting of 60 students involved in sports extracurricular activities and 69 students not involved in non-sports extracurricular (age= 16.62 ± 0.77 y.o., height= 155.24 ± 5.15 cm, weight= 47.26 ± 8.29 kg, first menstrual period 12.49 ± 1.21 y). The present study employed instruments socio-demographic characteristics, as well as validated questionnaires on menstrual hygiene practices, premenstrual syndrome (PMS), and mood swings. Result: The results showed that poor menstrual hygiene practices in students who participated in extracurricular sports with those who did not participate in sports activities were 29 and 35 students, respectively. Students who were involved in non-sports activities exhibited more severe and moderate symptoms of PMS compared to sports students. Additionally, sports students experienced more positive mood swings, while non-sports students reported more negative mood swings. Furthermore, significant differences between female students engaged in sports and those involved in non-sports extracurricular activities were only found in mood swings, neither in menstrual hygiene practices (0.910) nor PMS symptoms (0.776). Conclusion: Schools should promote female students' participation in sports to enhance their emotional well-being. Additionally, they should emphasize menstrual hygiene education and awareness to ensure proper practices among all students. Developing targeted interventions to help students manage PMS symptoms and maintain positive mood swings is also crucial for improving menstrual health and emotional well-being among adolescents.